Students Ability in Constructing Paragraph of Recount Text - Wardani, Rizqi Claudia; Nursalim, Nursalim; Samsur, Fadlia Ramadhani (INTERACTION: Jurnal Pendidikan Bahasa, 2019)
Writing skills is one type of language skills which should be controlled by the student. The students must be familiar with English especially to writing skill which write about their experience at the past time or to write recount text. For this reason, the researcher intended to investigate the students’ ability in constructing paragraph of recount text. The objective of this research is to measure students’ ability in constructing paragraphs and find out the causes of error made by the students. The design of this research is quantitative decriptive to measure students ability in constructing paragraphs at recount text. The population was students Madrasah Aliyah Negeri Model Sorong Grade XII. The technique of collecting data, the students were assigned to write the paragraphs in personal recount text based on their experiences in 60 minutes so the students decided the theme by themselves. The result of this research shows that 10 students score 43,4 % in good, then the students category of average was 9 students (39,1 %), and the students category of excellent was 4 students (17,1 %). The writer concluded that the students ability in constructing paragraph was average.